AN ANALYSIS OF LANGUAGE STYLE CLASSIFICATION IN THE LITTLE PRINCE NOVEL - Enzelina Napitupulu; Rina Octavia Simarmata; Carolina Pakpahan (Jurnal Scientia, 2023)
The aim of this research is to determine the types of language styles as part of linguistics. Here the focus of the study is language style. This research uses a qualitative descriptive approach and the research design is observational analysis. The data is in the form of novel text and the data source is the novel The Little Prince by Antoine and Library Research. This research is based on the theory of Gorys Keraft 2020. In this researcher the author uses the novel The Little Prince by Antoine. Researchers found several problems, namely 2 problems, the first is which language style is the most dominant, the second is what types of language styles are found in the novel. In this novel, the most dominant language style is contradiction with 21 data with a percentage of 30%. There are four types of language styles used in the novel The Little Prince by Antoine, namely the first is comparative, the second is affirmation, the third is satire, and the last is contradiction. The number of sentences is 70 data in the novel The Little Prince. In research findings there are percentages and frequencies in the essay, in the first type of language style comparative 16 frequency and 23%, second affirmation 15 frequency and 20%, third satire 18 frequency and 25%, fourth 21 frequency and 30%. the total number of data is 70 and the percentage is 100%